Fossiliferous Localities of the Pirabas Formation (Lower Miocene) - Távora, Vladimir de Araújo; Santos, André Augusto Rodrigues dos; Neto Araújo, Raphael (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2010)
The Pirabas Formation occurs in twenty-seven geographic localities in the Pará, Maranhão and Piauí states, where has been recorded in outcrops along coastal cliffs, roadcuts, mines and in the underground. In this paper, for the first time, the localities were located in map and georeferentiated, its macrofossiliferous content recorded, and the researchers that studied the specific geographic village were listed.
Keywords: Fossiliferous localities; Early Miocene; Pirabas Formation